Water liquid structure as studied by Raman and hyper-Raman spectroscopy - Hamaguchi, Hiro-O (2020)
Despite extensive studies over the years, anomalous behavior of water as a liquid still remains a mystery. We challenge this mystery by state-of-theart Raman and hyper-Raman spectroscopy.